DAMPAK INVESTASI STARBUCKS COFFEE TERHADAP PENJUALANPRODUKSI KOPI LOKAL DI INDONESIA - Meriza Sastri Nenda; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In terms of the domestic economy of a country, foreign companies or have significant influence. For example, the presence of starbucks i which one is a multinational entreprise corporation. In addition to providing benefits for their country Starbucks kiosks are established in various kinds of places in Indonesia of course there are also some disadvantages that arise. Losses arising in the social field carried by the company Starbucks itself is their consumer behavior.This research was used comparative advantage where people tend to prefer to buy products Starbucks just because the product was derived from foreign companies and has international labels as well as consumption of the product is done to show the social strata in life community. It was the indirect effects that are not good local coffee production in the country itself and be detrimental to farmers to local entrepreneurs in the country. Starbucks invesment growth was affected for a local coffee prices. Instability of the local coffee prices for farmers confused indeterming the income of coffee beans that wether or not a request and many or not request. Key words: Starbucks, Coffe, Farmers